THE MODERATING ROLE OF PROFITABILITY ON GOOD CORPORATE GOVERNANCE AND SUSTAINABILITY REPORT DISCLOSURE - Sari Mujiani; Nurmala Ahmar; Darmansyah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
A sustainability report is a voluntary report that demonstrates a company'ssocial and environmental responsibilities. Sustainability reports are required sothat stakeholders, such as the general public, are aware of the company'senvironmental responsibilities. Within a corporation or organization, corporategovernance refers to a set of procedures, policies, regulations, regulations, and guidelines. Corporate governance may also be defined as a concept that aimsto improve openness and accountability in order to ensure that the company'sgoals are met. The goal of this research is to investigate the moderatinginfluence of profitability in the sustainability report's Good CorporateGovernance. A quantitative research method was applied in this study.Purposive sampling was utilized in this study. The mining sector businesseslisted on the Indonesia Stock Exchange that publish sustainability reports andfinancial reports between 2013 and 2019 were the sample used in this study.The findings revealed that institutional ownership had a beneficial impact onthe sustainability report, however the independent board of commissioners andaudit committee had no impact. This study also suggests that profitability as amoderator can have a good impact on the sustainability report, as well asboosting the role of institutional ownership. Meanwhile, profitability as amoderator has had no impact on the sustainability report's independent boardof commissioners and audit committee